KAJIAN STATUS DMFT, PENGETAHUAN, SIKAP, SERTA PERILAKU IBU HAMIL TENTANG KESEHATAN GIGI DAN MULUT - Diana Haifa Zahra; Muhammad Rakha Galih Firmansyah; Soraya Fatimah; Ika Kusuma Wardani (Dentin, 2026)
Background: Oral health in pregnant women often declines due to physiological changes during pregnancy. Poor oral health maintenance behavior may increase the risk of dental caries and periodontal disease, which can affect both maternal and fetal health. Purpose: This study aimed to determine the DMFT status as well as the level of knowledge, attitudes, and oral health behaviors among pregnant women at Karang Mekar Public Health Center. Methods: This study was a descriptive observational study with a cross-sectional approach. The sample consisted of 30 pregnant women selected using an accidental sampling technique. Data were collected through questionnaires assessing knowledge, attitudes, and oral health behaviors, followed by clinical examination of the DMFT index. Data were analyzed descriptively and presented in the form of frequency distribution, percentages, and mean values. Results: The results showed that most respondents had a good level of knowledge (63.33%), while attitudes and behaviors were mostly categorized as moderate, accounting for 76.67% and 70.00%, respectively. Most respondents had visited a dentist more than six months prior and still tended to utilize dental services curatively rather than preventively. The mean DMFT index was 4.1, categorized as moderate, with the decay component being higher than the missing and filling components. Conclusion: Pregnant women at Karang Mekar Public Health Center had a relatively good level of knowledge; however, their attitudes and oral health maintenance behaviors were still not optimal, as reflected by the high decay component in the DMFT index.Keywords : dental caries, DMFT, pregnant women, sustainable development goals